The mystery of God's will : what does He want for me? - Swindoll, Charles R. 1934- (Word Pub, 1999)
We all face difficult decisions. How can we know that the decisions we make are in God's will? Swindoll examines this long debated subject from a balanced, biblical perspective regarding his own doubts and experiences. For anyone who's ever doubted God's will, or for those who are convinced of it in every situation, this book will be a real eye-opener.